Peripheral Oxytocin Predicts Higher-Level Social Cognition in Men Regardless of Empathy Quotient - Deuse, Lisa; Wudarczyk, Olga; Rademacher, Lena; Kaleta, Peter; Karges, Wolfram; Kacheva, Stella; Gründer, Gerhard; Lammertz, Sarah E. (Pharmacopsychiatry, 2019)
Introduction Pharmaceutical oxytocin (OT) administration is being tested as a novel treatment for social deficits in various psychiatric populations. However, little is known about how naturally occurring variation in peripheral OT relates to differences in social cognition. This study investigates whether healthy individuals with very high or very low levels of empathy differ in endogenous OT and whether OT plasma levels can predict performance in a mentalizing task.Methods 40 healthy men were included based upon their score above the 85th or below the 15th percentile of the empathy quotient inventory 1. Participants’ abilities to interpret social information was assessed via the Social Detection Task 2. Plasma OT levels were analyzed using enzyme immunoassay.Results OT plasma levels predicted mentalizing performance for more ambiguous social scenes (i. e., difficult items) for all participants. We found no group differences in OT plasma levels between subjects with high and low empathy.Discussion These findings confirm a link between peripheral OT and the ability to read subtle nonverbal social cues in healthy individuals, which is independent of self-reported empathy.
Keywords: social cognition; empathy; oxytocin